REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TGT PADA MATERI PERPINDAHAN KALOR DI SMP - Utami, Fitria; S, Stephanus Sahala; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aimed of this research was to determine the effectiveness of the cooperative learning model of Teams Games Tournament (TGT) in the remediation of students? misconceptions on heat transfer material in class VII at SMP Negeri 3 Kubu Raya. This study was a pre-experimental one group pretest-posttest design. The sample of this research was student of VII A consisting of 29 students. Ten items of multiple choice diagnostic test with open reasion used as research instrument. Test reliability (0,43 classified as medium). The result of this research was the concept that experienced the most misconception was heat transfer by convection. Percentage of average reduction in students? misconceptions per concept is 50,3%. While the value of the proportion to implementation the THT cooperative learning model was 0,50 and according to the barometer hattie the effectiveness level was classified as medium. The learning model TGT can be implemented into use as an alternative to remediate the students? misconceptions and increase student activity.Keywords: Remediation, Misconception, Teams Games Tournament, Heat Transfer